A Case of Congenital Facial Nerve Palsy with Microtia: Life Sciences-Pediatrics - Sundari, S.; Srinithi, R. (International Journal of Life Science and Pharma Research, 2022)
Congenital facial nerve palsy is defined as the presence of seventh cranial nerve palsy at birth or shortly thereafter. It occurs due to paralysis of muscles of facial expressions. It is mostly developmental or due to birth trauma. It is rare to be born with unilateral facial nerve palsy with associated ear anomaly, and hence determining the etiology is pivotal in accessing the prognosis and for selecting the right treatment for better outcome. In this case, a child is born with unilateral left -sided lower motor neuron type facial palsy, along with left sided microtia with no history of birth trauma or any associated congenital anomalies. Therefore, it is of developmental origin and does not fit into any syndromic diagnosis with an magnetic resonance imaging brain showing normal facial nerve anatomy. Child had little improvement in facial expressions with better eye closure with regular physiotherapy. Facial reanimation surgeries can be done either in preschool or adolescent period depending on the child’s condition. In this case, the child is being managed conservatively until he is fit enough to perform facial reanimation surgeries.